2015
DOI: 10.1890/14-0422.1
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of habitat suitability, dispersal, and fragmentation on the distribution of river fishes

Abstract: Habitat suitability, dispersal potential, and fragmentation influence the distribution of stream fishes; however, their relative influence and interacting effects on species distributions are poorly understood, which may result in uncertain outcomes of river rehabilitation and conservation. Using empirical data describing 17 relatively common stream fishes, we combine (1) species habitat suitability models (MaxEnt) with a (2) species dispersal model (FIDIMO) and a (3) worst-case scenario of the influence of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 42 publications
1
47
2
Order By: Relevance
“…This finding is in contrast to recent studies that found artificial barriers were generally not important in explaining the distribution of riverine fish in some study systems (Branco, Segurado, Santos, Pinheiro, & Ferreira, 2012;Radinger & Wolter, 2015). This finding is in contrast to recent studies that found artificial barriers were generally not important in explaining the distribution of riverine fish in some study systems (Branco, Segurado, Santos, Pinheiro, & Ferreira, 2012;Radinger & Wolter, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in contrast to recent studies that found artificial barriers were generally not important in explaining the distribution of riverine fish in some study systems (Branco, Segurado, Santos, Pinheiro, & Ferreira, 2012;Radinger & Wolter, 2015). This finding is in contrast to recent studies that found artificial barriers were generally not important in explaining the distribution of riverine fish in some study systems (Branco, Segurado, Santos, Pinheiro, & Ferreira, 2012;Radinger & Wolter, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the higher mean effect on macroinvertebrate abundance ( r = 0.21) compared to richness ( r = 0.08) reported in Miller et al (2010) and recent empirical and modelling studies which showed that the species pool and source populations for colonization are often sparse and limit the effect of restoration on species richness (Radinger and Wolter, 2015;Stoll et al, 2014;Tonkin et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…As shown by our analysis, accounting for dispersal limitation in predicting where a species could occur is therefore important, because although suitable habitat may be available, the ability of a species to migrate to that habitat is critical in determining their occurrence. For example, Radinger and Wolter () found that the dispersal ability of river fishes is more than four times more important as a predictor than habitat suitability for determining species presence at a particular location. Although ants disperse seeds of Pulmonaria species, taxon‐specific differences in ant ability to disperse seeds and whether different Pulmonaria species use different ant taxa to disperse seeds remain to be tested.…”
Section: Discussionmentioning
confidence: 99%